EARLY CHILDHOOD ENVIRONMENTAL LITERACY PROJECT at TK. CITRA KUSUMA 1 - Hafizhah, Hanan Muthiah (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to examine the implementation of project “Aku Sayang Bumi” at Citra Kusuma Kindergarten using qualitative methods. The qualitative method was chosen to gain an in-depth understanding of the project implementation process and how Pancasila values, especially love and care for the environment, are internalized in early childhood learning activities. Data were collected through participatory observation, interviews with teacher and students, and documentation of learning activities. Data were analyzed descriptively to describe in detail the implementation of the project. The results show that the project is effective in fostering awareness and positive attitudes towards environmental conservation, while strengthening the character of students in accordance with Pancasila student profile. This research provides recommendations for the development of learning programs that integrate Pancasila values and environmental education at the early childhood education level.